The Law Collection (formerly the Law Library) of Library and Instructional Media Services at the College of the Bahamas - Adams, Errol Augustus (International Journal of Bahamian Studies, 2015)
The Law Collection of the Harry C. Moore Library and Information Centre was first established in August 2000 at the time that the College of The Bahamas entered into a collaborative LL.B programme with the University of the West Indies. This paper profiles the law librarians, the Law Collection and the UWI/COB programme.